A direct methanol–hydrogen peroxide fuel cell with a Prussian Blue cathode. (9th March 2016) - Yan, X.H.; Zhao, T.S.; An, L.; Zhao, G.; Shi, L.
Abstract: In this work, a direct methanol–hydrogen peroxide fuel cell is developed and tested. Theoretically, it is shown that the use of hydrogen peroxide in a direct methanol fuel cell (DMFC) not only increases the cell's voltage from 1.21 V to 1.76 V, but also reduces the activation loss of the reduction reaction as a result of two-electron transfer. Experimentally, it is demonstrated that the fuel cell with the use of an inexpensive carbon nanotube supported Prussian Blue catalyst, exhibits a peak power density of 125 mW cm −2 at 60 °C, which is comparable to that of conventional DMFCs with platinum-based catalysts. Highlights: A direct methanol–hydrogen peroxide fuel cell is developed. The theoretical voltage of this fuel cell reaches 1.76 V. Prussian Blue/CNT catalyst is prepared for the reduction reaction of H2 O2 . This fuel cell yields a peak power density of 125 mW cm −2 at 60 °C.